PENGARUH EKSTRAK DAUN GAMBIR TERHADAP HAMA TERONG KB, Epilachna varivestis MULSANT - ADRIA ADRIA (Pusat Penelitian dan Pengembangan Perkebunan, 1998)
Effect of gambir leaf extract on the terong KB pest Epilachna varivestis MulsantThe utilization of synthetic insecticides to control pests has caused some problems, so that it is necessary to ind out some biopesticides to control diem. The chemical contents of the gambire plant (Uncaria gambir Roxb) are katcchine. tanin catecu (tannat), flouresine, and kucrsitine These chemical contents are potential for biopesticide. Therefore, research on the application of gambire leaf extract on the pest of terong KB was conducted in IPPTB I.aing, Solok, West Sumatera. The research used a completely randomized design with five replications. The treatments were gambire leaf extract at the concentrations of 250, 500, I 000, 1 500 ppm, and 0 ppm (without leaf extract as the control), lbe results of the research indicated that gambire leaf extract has an insecticide charactic on E varivestis, whee the most efective concentration was I 500 ppm which caused larvae mortality at I, II, III, IV instars, and imago 52.20% 50.40% 40.80% 36.80% and 11 35%. Besides, it also caused the decease in egg hatches and the change of pupae into imagoes of about 32.59% and 37.98% respectively. The efect of the leaf concentrations above resulted in the lie cycle period of the pest, eating habit of the larvae and ecundity level of the imagoes.